Evaluation of a quantitative measurement of suprapatellar effusion by ultrasonography and its association with symptoms of radiographic knee osteoarthritis: a cross-sectional observational study. Issue 1 (December 2016) - Chiba, Daisuke; Tsuda, Eiichi; Maeda, Shugo; Sasaki, Eiji; Takahashi, Ippei; Nakaji, Shigeyuki; Ishibashi, Yasuyuki
Abstract Background Quantitative measurement of knee joint effusion by ultrasonography has not been well established; however, a categorical measurement (e.g., a ≥4-mm-deep suprapatellar pouch) is recommended. Therefore, the current study aimed to elucidate the association between symptoms of knee osteoarthritis (OA) and the quantitative measurement of suprapatellar effusion by ultrasonography. Methods One hundred twenty-seven volunteers participated (31 men and 96 women; mean age: 68.3 ± 9.8 years; body mass index: 23.2 ± 3.0 kg/m2 ). The Kellgren-Lawrence grades (KLGs) of both knees were assessed; all subjects had definitive osteoarthritic change (KLG ≥2) in both knee joints. Joint effusion was evaluated using an ultrasound probe, which was placed longitudinally on the suprapatellar pouch, and we determined the area (mm2 ) of the echo-free space. Then we summed the effusion area of both knees. All subjects answered the knee injury and osteoarthritis outcome scale (KOOS) questionnaire. Multiple linear regression analysis was conducted to elucidate the association between the summed value of the knee effusion area and the KOOS subscales, which were adjusted by age, sex, body mass index, and KLG. Results Of 254 knees, 180 were KLG 2, 57 were KLG 3, and 17 were KLG 4. The multiple regression models showed that the quantitative knee effusion area significantly correlated with the following KOOS subscales: pain (B = −0.057;β = −0.253;P = 0.002), symptom (B = −0.053;β = −0.251;P = 0.002), sport and recreation (B = −0.069;β = −0.205;P = 0.007), and quality of life (B = −0.083;β = −0.276;P = 0.001). Conclusion In this cross-sectional study, the quantitative measurement of suprapatellar effusion by ultrasonography was associated with symptoms of radiographic knee OA.